Psycho-behavioural factors associated with medication adherence among male outpatients with hypertension in a Ghanaian hospital - Kretchy, I.A.; Boima, V.; Agyabeng, K.; Koduah, A.; Appiah, B. (Plos One, 2020)
Medication adherence is a key health outcome that reflects the health and general wellbeing of patients with hypertension. Challenges with adherence are common and associated with clinical, behavioural and psychosocial factors. This study sought to provide data on the extent of medication adherence among male patients with hypertension and their biopsychosocial predictors. Patient and clinical characteristics, psychological distress, insomnia and sexual dysfunction were hypothesized to predict outcomes of medication adherence. Utilizing quantitative data from a hospital-based cross-sectional study from 358 male out-patients with hypertension attending a tertiary hospital in Ghana, medication adherence was associated with age, marital status, educational level, income, duration of diagnosis, number of medications taken and sexual dysfunction. These findings support the need for biopsychosocial interventions aiming at promoting adherence while taking these factors into consideration for the benefit of improving the health and general well-being of male patients with hypertension.
Research Article
Keywords: Medication; psychosocial factors; psychosocial factors; sexual dysfunction